Auditory Distance Rendering Based on ICPD Control for Stereophonic 3D Audio System - Jeon, Se-Woon; Park, Young-Cheol; Youn, Dae Hee (IEEE signal processing letters, 2015)
In this letter, we propose a new auditory distance rendering (ADR) algorithm based on the interchannel phase difference (ICPD) control. In the conventional ICPD control, distance perception of the sound image is nonlinearly controlled, and directional localization of the sound image can be biased by changes of the interaural cues. These problems are caused by applying the frequency-independent ICPD without considering the acoustic transfer paths of the system setup. To solve these problems, first, the interaural cues of ear signals are analyzed by binaural auditory simulations. Then, stereophonic ADR filters are designed that produce ear signals with a linearly controlled interaural cross-correlation (IACC) and a consistent interaural level difference (IALD) for sophisticated distance perception under the given stereo setup. Subjective test results show that the proposed algorithm can provide better distance controllability than the conventional method with reduced lateralization blur of the sound image.